RELATIONSHIP BETWEEN UNIVERSITY ADMISSION SELECTION AND ACADEMIC PREDICTION IN MEDICAL STUDENTS - Pradnyana, I Putu Yudi; Darmayani, I Gusti Ayu Sri; Sundariyati, I Gusti Ayu Harry; Manuaba, Ida Bagus Ametha Putra (E-Jurnal Medika Udayana; Vol 14 No 03 (2025): E-Jurnal Medika Udayana, 2025)
Selection of new students at the undergraduate level in public universities is carried out in 3 selection pathways, namely SNMPTN, SBMPTN, and Mandiri. Selection of student admission exams will affect the quality of students which can be measured by student academic achievement, including GPA and academic competition winners. The purpose of this study was to see the differences in academic achievement and the relationship between admission pathways and student academic achievement. This study is an analytic study through a cross-sectional approach conducted at the Faculty of Medicine, Udayana University. The data are in the form of primary data and secondary data. Data processing and analysis using STATA 12.0 application. The analysis was conducted in the form of univariate analysis to describe the characteristics and bivariate to see the relationship between variables. Students with a GPA of 3.50 were more accepted through the SBMPTN pathway, while GPA 3.01 - 3.50 were more accepted through the Mandiri pathway. Students who were accepted through the SBMPTN pathway had more achievements in the form of academic competition winners compared to other admission pathways. This study concluded, it was concluded that there were differences in students’ academic achievement with the most achievements found in students admitted through the SBMPTN pathway. There is a relationship between admission selection pathway and academic achievement consisting of student GPA and academic competition winners. Students who are accepted through the SBMPTN pathway have a greater chance of achieving high GPA and winning academic competitions than other pathways.